EXPLORING TEACHERS’ CHALLENGES IN ENGAGING WITH ONLINE COMMUNITIES FOR CONTINUING PROFESSIONAL DEVELOPMENT - Peter Babajide Oloba; Tendayi Dzinoreva (Universitas Labuhanbatu, 2026)
Purpose – This study aimed to explore the challenges teachers experience when engaging in online communities for CPD, with particular focus on how these challenges influence teacher identity and voice.Methodology – A qualitative research approach, grounded in a constructivist paradigm, was adopted. Data were collected from 100 teachers through an open-ended questionnaire, followed by semi-structured interviews with 20 purposively selected participants. The data were analyzed using thematic analysis.Findings – The findings revealed six key challenges: internet connectivity, information overload and misinformation, inadequate digital skills, time constraints, contextual disconnect, inadequate diversity, and lack of leadership support. These findings demonstrate that while online CPD offers opportunities for collaboration and professional growth, structural, technological, and institutional barriers limit active participation, knowledge construction, and identity development.Contribution – This study contributes to the understanding of online CPD by critically highlighting how structural, technological, and institutional barriers shape teachers’ engagement, identity, and voice in digital professional learning spaces. It extends the Communities of Practice framework by demonstrating that participation in online environments is contextually constrained and uneven, rather than inherently inclusive. Furthermore, the study provides practical and policy-relevant insights for designing more equitable, context-responsive, and supportive online CPD systems.